Oestetrol stimulates proliferation and oestrogen receptor expression in breast cancer cell lines: Comparison of four oestrogens. (February 2015) - Liu, Shunyu; Ruan, Xiangyan; Schultz, Silke; Neubauer, Hans; Fehm, Tanja; Seeger, Harald; Mueck, Alfred O.
Abstract Objectives Oestetrol (15-alpha-hydroxyoestriol, E4) is an endogenous oestradiol metabolite mainly produced at high concentrations in the fetal liver. In earlier studies E4 was investigated for its use as marker for pregnancies at risk, especially with vascular problems. Some current investigations suggest that the use of E4 in hormone therapy or contraception may have advantages in terms of breast cancer risk when compared to other oestrogens. Methods Proliferation of two oestrogen receptor-positive breast cancer cell lines (ZR 75-1 and HCC 1500) was investigated after incubation with oestrone (E1), oestradiol (E2), oestriol (E3), and oestetrol (E4). Receptor expression of oestrogen receptor-alpha (ERα) and -beta (ERβ) was determined by Western-Blot. Results All four oestrogens elicited a significant proliferative stimulation at concentrations of 10−10 und 10−9 M as compared to controls. Oestrone displayed a significantly weaker effect than E2. Oestetrol was significantly less effective than E2 at the lower concentration. Expression of ERα and ERβ was significantly upregulated by all oestrogens tested, without differences between the latter. Conclusions Our results indicate a slightly lower proliferative effect of E4, but only at low concentrations. However, no difference was found regarding receptor expression. Breast cancer risk associated with use of oestetrol should be tested in clinical trials.